Proceedings of the 2009 ACM/IEEE International Symposium on Low Power Electronics and Design 2009
DOI: 10.1145/1594233.1594258
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thermal management using thin-film thermoelectric cooling

Abstract: Multi-core architectures require Dynamic Thermal Management mechanisms (DTM) to handle (1) multiple hotspots and (2) global chip heating effect while finding the best trade-off between performance and thermal control. In that scenario Thin-Film Thermoelectric Cooling devices can be used to mitigate both effects since they provide on-die localized cooling with a dynamic and heterogeneous effect. This work proposes controlling TFTECs from the microarchitecture for an enhanced Dynamic Thermal Management in multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Long et al propose a system-level design to optimize bias current and placement of on-package TECs based on application of greedy algorithms and a modified compact thermal models of the TEC interfaces [4]. Chaparro et al examine on-die thermal management techniques such as Dynamic Frequency and Voltage Scaling (DVFS) [5]. Sri Choday et al describe methodologies for optimization of material properties of TE devices to augment their cooling properties [6].…”
Section: Related Workmentioning
confidence: 99%
“…Long et al propose a system-level design to optimize bias current and placement of on-package TECs based on application of greedy algorithms and a modified compact thermal models of the TEC interfaces [4]. Chaparro et al examine on-die thermal management techniques such as Dynamic Frequency and Voltage Scaling (DVFS) [5]. Sri Choday et al describe methodologies for optimization of material properties of TE devices to augment their cooling properties [6].…”
Section: Related Workmentioning
confidence: 99%
“…A TE Cooler (TEC) operates on the basis of the Peltier effect that helps to reduce the junction temperature by dumping heat from the cold side to the hot side when a current flows through it [1][2][3][4][5][6]. The integration of Bi 2 Te 3 based thin film super-lattice TECs within microprocessor package has been experimentally demonstrated [2].…”
Section: Introductionmentioning
confidence: 99%
“…The design and run-time approaches for integration of TEC are also being explored. Long et al have explored algorithms for optimal placements of TECs in a chip to maximize the cooling efficiency [3,4]. The applications of TECs in dynamic thermal management of microprocessors have been studied [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…TE modules made of miniaturized bulk Bi 2 Te 3 were also studied for dynamic thermal management in a multicore chip where one or more cores were augmented with TE devices to increase their performance [4]. Simulation studies showed that a 16-core processor could achieve performance that was within 8% of a thermally unconstrained processor [4] when multiple TE devices are placed on the die.…”
mentioning
confidence: 99%
“…Simulation studies showed that a 16-core processor could achieve performance that was within 8% of a thermally unconstrained processor [4] when multiple TE devices are placed on the die. Hence, TE devices are also promising for chip performance enhancement.…”
mentioning
confidence: 99%